First, multiply each term within the right parenthesis by the term on the left:
(color(red)(3sqrt(x^3))) xx (4 + 2sqrt(xy)) =>
(color(red)(3sqrt(x^3)) xx 4) + (color(red)(3sqrt(x^3)) xx 2sqrt(xy)) =>
12sqrt(x^3) + 6sqrt(x^3)sqrt(xy)
Next, we can use this rule to combine the radicals in the term on the right:
sqrt(color(red)(a)) * sqrt(color(blue)(b)) = sqrt(color(red)(a) * color(blue)(b))
12sqrt(x^3) + 6sqrt(color(red)(x^3))sqrt(color(blue)(xy)) =>
12sqrt(x^3) + 6sqrt(color(red)(x^3) * color(blue)(xy)) =>
12sqrt(x^3) + 6sqrt(x^4y)
Then, we can use the opposite of the above rule to reduce the radicals:
sqrt(color(red)(a) * color(blue)(b)) = sqrt(color(red)(a)) * sqrt(color(blue)(b))
12sqrt(x^3) + 6sqrt(x^4y) =>
12sqrt(color(red)(x^2) * color(blue)(x)) + 6sqrt(color(red)(x^4) * color(blue)(y)) =>
12sqrt(color(red)(x^2))sqrt(color(blue)(x)) + 6sqrt(color(red)(x^4))sqrt(color(blue)(y)) =>
12xsqrt(x) + 6x^2sqrt(y)